Divorce : Crisis, Challenge, Or Relief? - Galston, William A.; Galston, William A.; Chiriboga, David; Chiriboga, David (Book collections on Project MUSE., 1991)
Not since William Goode's Women in Divorce in the 1950's have we had such a comprehensive study of adjustment to divorce. This longitudinal work views divorce as a transition process which may have positive or negative outcomes over time. In addition to statistical analysis, the book includes very interesting case studies to demonstrate the dynamic events occurring as individuals refashion their lives after the breakup of their marriages. Researchers on divorce and the interested public will find this book very valuable for years to come."-Colleen L. Johnson, Ph.D.ProfessorMedical Anthropology, University of California, San Francisco We are witnessing a steady increase in the overall number of older adults who are divorced, yet the majority of divorce research has concerned itself with persons in the younger adult years. This unique, groundbreaking book addresses the critical need for information on the impact of divorce on individuals in all age groups, and pays special attention to age as a factor in the effects of divorce on both men and women. Written by an interdisciplinary team of social and behavioral scientists, Divorce: Crisis, Challenge or Relief? provides the invaluable results gained from their life span study of divorced adults. Divorce is the product of hundreds of interviews containing a host of very specific questions conducted with divorced adults between the ages of 20 and 79, both just after their divorce and again several years later.